2018
DOI: 10.1089/lrb.2017.0027
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Therapy Using Bone Marrow-Derived Mononuclear Cells in Treatment of Lower Limb Lymphedema: A Randomized Controlled Clinical Trial

Abstract: Stem cell therapy can achieve improvement in limb circumference as well as pain relief and improvement in walking ability in patients with chronic lymphedema compared with those in control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…Figure 4 In a similar recent study, Ismail et al discovered that BDRCs also increased the efficacy of CDT in primary lower limb lymphedema. 16 However, this study too may have been subject to performance bias, namely, a systematic difference in exposure to compression therapy between the BDRC and CDT groups. Compression therapy is a known confounder for volume reduction in lymphedema, as significant volume reduction can be credited to this treatment alone.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Figure 4 In a similar recent study, Ismail et al discovered that BDRCs also increased the efficacy of CDT in primary lower limb lymphedema. 16 However, this study too may have been subject to performance bias, namely, a systematic difference in exposure to compression therapy between the BDRC and CDT groups. Compression therapy is a known confounder for volume reduction in lymphedema, as significant volume reduction can be credited to this treatment alone.…”
Section: Discussionmentioning
confidence: 95%
“…4 Overall, we did not find the adipose-derived treatment to decrease the volume of lymphedema, whereas other studies have found considerable reduction. [14][15][16] However, these studies all used bone marrow-derived regenerative cells (BDRCs); these cells also stem from the mesenchymal progenitor line and have regenerative properties comparable to adipose-derived cells. [17][18][19] Maldona et al showed that BDRC treatment without compression sleeve was as effective as compression sleeve alone in decreasing BCRL volume.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the outcomes of cell-based therapy on patients with lymphedema and the results are promising (Table 1). [106][107][108][109][110][111] Maldonado et al randomized 20 patients with breast cancer-related lymphedema (BCRL) to receive intramuscular BMSC injection in the affected arm (n = 10) or traditional compression therapy (n = 10). At a follow-up of 12 weeks, both groups showed a similar reduction in lymphedema volume.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Other stem cells may also play a role in the treatment of lymphedema, but little research has been done. Mononuclear cells (MNCs) can potentially alleviate lymphedema through stimulation of lymph‐angiogenesis 60 . Spitalieri et al .…”
Section: Therapeutic Effect Of Stem Cell In Lymphedemamentioning
confidence: 99%
“…Mononuclear cells (MNCs) can potentially alleviate lymphedema through stimulation of lymph-angiogenesis. 60 Spitalieri et al explored generation of human-induced pluripotent stem cells (hiPSCs) derived from autologous extra-embryonic fetal tissues. This innovative personalized regenerative technology can transform cells into embryonic stem-like cells.…”
Section: Stem Cell Therapy For Lymphedemamentioning
confidence: 99%